Metalepsa jako strategia narracyjna w dziełach literackich i filmowych (analiza zjawiska na wybranych przykładach) - Karkiewicz, Magdalena (Załącznik Kulturoznawczy, 2023)
Logically forbidden transition, the impossible transgression, fictional characters moving through the boundaries between levels of (un)reality and the attempt to cross the ‘frames’ of artistic presentation constitute the essence of the subject of this dissertation: the metalepsis. This term, originally derived from the rhetoric, was annexed to narratology field in 1972 by a French theoretician, Gérard Genette. In his book Figures III, he described a narrative metalepsis (ʻla métalepse narrativeʼ) as ʻany intrusion by the extradiegetic narrator or narratee into the diegetic universe (or by diegetic characters into a metadiegetic universe, etc.), or the inverse.ʼ The definition became a starting point for further research on metalepsis, which in recent years has gained particular popularity in Western Europe. It was noticed that metalepsis is particularly characterized by the comic potential and Woody Allen’s movie ‘Purple Rose of Cairo’ is a perfect example of it. However, the influence range of this figure seems to go far beyond the mere evocation of emotions. The analyzed examples of the use of metalepsis as a narrative strategy, for example a short story written by Julio Cortázar The Continuity of Parks, have emphasized the specificity of impact of this figure on the recipient. By corresponding with such phenomena as ʻmise en abymeʼ or ʻtext in the textʼ, metalepsis draws attention to the recipients, the readers or the viewers themselves and puts them in ontological uncertainty concerning their own existence. Since heroes of the fictional worlds can move between levels of diegesis, leave the novel or the cinema screen, read the book about their own fate or suddenly realize that they are the imaginary creatures created by some higher creative’s instance and ruled by a higher order, then how can we be sure that we are for r e a l ?